IMPLEMENTASI GREEN ACCOUNTING DAN CSR MEMPENGARUHI ROE DAN PER DIMODERASI SUSTAINABILITY DISCLOSURE - Ade Nahdiatul Hasanah; Tri Wahyuni Sukiyaningsih; Ambar Putriani (Universitas La Tansa Mashiro, 2024)
This study focuses on testing the effect of the implementation of green accounting and corporate social responsibility there is financial performance represented by return on equity and market performance represented by price earning ratio moderated by sustainability disclosure. The companies studied are companies with the highest liquidity value indexed by kompas 100 during the period 2020-2022, samples are needed through the criteria process (purposive) and produced by 31 companies so that 93 data processed using SPSS Ver 23 are obtained. Methods of analysis include descriptive analysis, classical assumption test and hypothesis test with moderating regression equation. There are 4 hypotheses that are decided and accepted statements: 1) implementation of green accounting and CSR affects ROE with R quare level of 3.4%, 2) implementation of green accounting and CSR affects PER with R quare level of 1%, 3) sustainability disclosure strengthens the implementation of green accounting and CSR affects ROE with R quare level of 4.4% and 4) sustainability disclosure tends to weaken the implementation of green accounting and CSR affects PER with R quare level of 1%.